2022
DOI: 10.1515/npprj-2022-0003
|View full text |Cite
|
Sign up to set email alerts
|

Bark from Nordic tree species – a sustainable source for amphiphilic polymers and surfactants

Abstract: Many of the amphiphilic molecules, or surfactants, are produced from fossil-based raw materials. With the increasing awareness of the climate situation, focus has shifted toward more environmentally friendly solutions to replace fossil-based products. This has led to more interest towards the forest. The circular bioeconomy is focused on making use of residues and waste and on optimizing the value of biomass over time via cascading. Nowadays, bark is seen as a waste product by industries and mainly incinerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…This view is supported by another research, which argues that the hydrophobic domains of a polyphenolic compound, tannin from Acacia mearnsii bark, are oriented toward the surface while the hydrophilic domains adsorb on cellulose . The bark of various Nordic tree species, in general, is rich in amphiphilic compounds . Similar to any polyphenolic compound, the WBE consists of hydrophilic parts (OH groups) and more hydrophobic parts (aromatic rings).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This view is supported by another research, which argues that the hydrophobic domains of a polyphenolic compound, tannin from Acacia mearnsii bark, are oriented toward the surface while the hydrophilic domains adsorb on cellulose . The bark of various Nordic tree species, in general, is rich in amphiphilic compounds . Similar to any polyphenolic compound, the WBE consists of hydrophilic parts (OH groups) and more hydrophobic parts (aromatic rings).…”
Section: Resultsmentioning
confidence: 88%
“… 58 The bark of various Nordic tree species, in general, is rich in amphiphilic compounds. 59 Similar to any polyphenolic compound, the WBE consists of hydrophilic parts (OH groups) and more hydrophobic parts (aromatic rings). However, more research is needed to verify the exact mechanism behind the observed synergistic effects of WBE and AKD.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding how it can be degraded in nature by different microorganisms is key for future valorization, for instance using select enzymes, and can also be of high relevance to limit the harmful effects of wood-boring insects. Bark from other species contain other types of extractives, with for example birch bark being enriched in betulin and pine in condensed tannins 41 , and our study sets a basis for investigating whether degradation also of other bark types progresses via initial degradation of key 'gatekeeper' molecules that strongly inhibit the growth of but a few extractive-detoxifying microbial species.…”
Section: Discussionmentioning
confidence: 95%
“…Spruce is indispensable to the forest industry and is used for pulp and paper production in the northern hemisphere. Looking only at the Nordic countries, bark is an industrial side stream produced in close to 400 million m 3 per year 41 , which today is poorly utilized. Understanding how it can be degraded in nature by different microorganisms is key for future valorization, for instance using select enzymes, and can also be of high relevance to limit the harmful effects of wood-boring insects.…”
Section: Discussionmentioning
confidence: 99%
“…Spruce is one of the dominant tree species in northern hemisphere forests and of high economic value, and its bark comprises around 10–15% of the volume at harvest. In the Nordic countries alone, bark is produced in close to 400 million m 3 per year 5 , but it is largely seen as an industrial side stream and is either left to rot in the forest or burnt for energy at the mill. In addition to wood polymers, spruce bark contains a high amount of lipophilic extractives, mainly resin acids (>10 mg/g dry bark), triglycerides (~8 mg/g), steryl esters (~5 mg/g), fatty acids (~2.5 mg/g), and sterols (~1.3 mg/g) (Fig.…”
Section: Introductionmentioning
confidence: 99%